2016
DOI: 10.1002/2016jd025251
|View full text |Cite
|
Sign up to set email alerts
|

The unstable ice nucleation properties of Snomax® bacterial particles

Abstract: Snomax® is often used as a surrogate for biological ice nucleating particles (INPs) and has recently been proposed as an INP standard for evaluating ice nucleation methods. We have found the immersion freezing properties of Snomax particles to be substantially unstable, observing a loss of ice nucleation ability over months of repeated droplet freezing measurements of the same batch of Snomax stored as dry pellets in a freezer. This reflects the fragility of the most ice active large protein aggregates and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
92
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 62 publications
(108 reference statements)
13
92
1
Order By: Relevance
“…A notable difference from the droplets containing illite is that there is significant weakening in ice nucleation ability as the concentration/surface area of Snomax is reduced. This behavior matches what is known regarding the low abundance of the most efficient but fragile Type I ice nucleating proteins that freeze at −3 to −2 • C vs. the more abundant and resilient but less efficient Type III proteins that freeze around −8 to −7 • C (Polen et al, 2016;Turner et al, 1990;Yankofsky et al, 1981).…”
Section: Using Critical Area Analysis To Predict Droplet Freezing Spesupporting
confidence: 71%
See 2 more Smart Citations
“…A notable difference from the droplets containing illite is that there is significant weakening in ice nucleation ability as the concentration/surface area of Snomax is reduced. This behavior matches what is known regarding the low abundance of the most efficient but fragile Type I ice nucleating proteins that freeze at −3 to −2 • C vs. the more abundant and resilient but less efficient Type III proteins that freeze around −8 to −7 • C (Polen et al, 2016;Turner et al, 1990;Yankofsky et al, 1981).…”
Section: Using Critical Area Analysis To Predict Droplet Freezing Spesupporting
confidence: 71%
“…Figure 6a shows decreasing concentration freezing curves for droplets containing Snomax particles. Snomax is a freeze-dried powder manufactured from nonviable Pseudomonas syringae bacteria and is commonly used to make artificial snow due to its very mild freezing temperature of −3 to −7 • C. Its ice nucleation properties are attributed to large protein aggregates, and Snomax is often used as a proxy for atmospheric biological INP (Pandey et al, 2016;Polen et al, 2016;Wex et al, 2015). A similar approach was undertaken in which g was retrieved using the highest concentration freezing curve (solid blue line).…”
Section: Using Critical Area Analysis To Predict Droplet Freezing Spementioning
confidence: 99%
See 1 more Smart Citation
“…The birchS sample seems to lose ice activity during storage, suggesting that care should be taken when comparing results of ice nucleation of biological samples because some samples could potentially change over time. A loss of ice activity over time has also been previously observed for Pseudomonas syringae (e.g., Polen et al, 2016).…”
Section: Results Of Immersion Freezing Measurementsmentioning
confidence: 63%
“…Biological particles such as Pseudomonas syringae bacteria can induce freezing in supercooled water at temperatures as high as −2 • C Polen et al, 2016;Wex et al, 2015). While mineral dust particles are the leading candidate for the most abundant ice nucleating particles (INPs) in the atmosphere (Hoose et al, 2008;, lidar and radar measurements (Bühl et al, 2013), as well as laboratory studies in which melted precipitation samples were refrozen (Christner et al, 2008;Petters and Wright, 2015;Vali, 1971Vali, , 1996, have shown that freezing can occur at temperatures higher than −12 • C. In this temperature range, no investigated mineral samples of atmospherically relevant particle sizes (or other atmospherically relevant non-biological particles) have exhibited detectable ice nucleating activity in Atkinson et al (2013), Cantrell and Heymsfield (2005), DeMott et al (2015), and Murray et al (2012).…”
Section: Introductionmentioning
confidence: 99%